Backyard Poultry Flocks in Morocco: Demographic Characteristics, Husbandry Practices, and Disease and Biosecurity Management - Asma Fagrach; Siham Fellahi; Mohammed Kamal Challioui; Oumaima Arbani; Ibtissam El Zirani; Faouzi Kichou; Mohammed Bouslikhane (Animals, 2023)
Backyard poultry farming is an important tool for poverty alleviation and food security in rural areas of Morocco. A descriptive epidemiologic survey was conducted in 286 backyard poultry flocks from the provinces of Khemisset and Skhirat-Temara to gain baseline data on the current status of backyard poultry flocks in Morocco as well as its potential implications on the transmission and spread of avian diseases. The findings indicated that 88.8% of flocks were raised in a mixed confinement system, with an average flock size of 30 birds (range 1–352). Chickens accounted for 83% of the overall reported birds. More than two-thirds of respondents (69%) kept chickens only, while the remaining flocks raising multiple bird species in total promiscuity. Diseases were the highest cause of mortality (84.7%), followed by predation (15.3%). According to 56.1% of the owners, respiratory symptoms were among the major disease signs reported, besides ectoparasite infestation. Flock health management revealed a lack of preventive vaccination, lack of veterinary consulting, lack of biosecurity practices, and irrational self-medication of diseased birds using antibiotics, pesticides, and hazardous chemicals that could be a significant health risk for consumers. The need for an outreach program about disease prevention and biosecurity practices, along with prophylactic campaigns, should be emphasized to further mitigate the risks of backyard poultry flocks on the commercial sector and public health.